A Potent HIV Protease Inhibitor, Darunavir, Does Not Inhibit ZMPSTE24 or Lead to an Accumulation of Farnesyl-prelamin A in Cells - Coffinier, Catherine (American Society for Biochemistry and Molecular Biology, 2008)
HIV protease inhibitors (HIV-PIs) are key components of highly active antiretroviral therapy, but they have been associated with adverse side effects, including partial lipodystrophy and metabolic syndrome. We recently demonstrated that a commonly used HIV-PI, lopinavir, inhibits ZMPSTE24, thereby blocking lamin A biogenesis and leading to an accumulation of prelamin A. ZMPSTE24 deficiency in humans causes an accumulation of prelamin A and leads to lipodystrophy and other disease phenotypes. Thus, an accumulation of prelamin A in the setting of HIV-PIs represents a plausible mechanism for some drug side effects. Here we show, with metabolic labeling studies, that lopinavir leads to the accumulation of the farnesylated form of prelamin A. We also tested whether a new and chemically distinct HIV-PI, darunavir, inhibits ZMPSTE24. We found that darunavir does not inhibit the biochemical activity of ZMPSTE24, nor does it lead to an accumulation of farnesyl-prelamin A in cells. This property of darunavir is potentially attractive. However, all HIV-PIs, including darunavir, are generally administered with ritonavir, an HIV-PI that is used to block the metabolism of other HIV-PIs. Ritonavir, like lopinavir, inhibits ZMPSTE24 and leads to an accumulation of prelamin A.